Applicability of A rotary eddy current damper in passenger vehicle suspension with parallel inerter - Soong, Ming Foong; Ramli, Rahizar; Saifizul, Ahmad Abdullah; Zamzamzadeh, Mahdieh (Science Publishing Corporation, 2018)
Numerous studies have proven that the performance of vehicle suspension can be benefited by an inerter in parallel to conventional spring-damper setup, yet its usability in passenger vehicle suspension is still limited by practical consideration in physical implementation. One way of achieving better physical implementation of the parallel inerter suspension layout is to exploit the inerter's flywheel as a metallic conductor to integrate passive damping in the form of a rotary eddy current damper. However, the feasibility of eddy current damping in this specific application remains unknown. This study investigates the applicability of eddy current damping incorporated in an inerter in terms of the achievable damping rates as required in typical passenger vehicle suspensions. In the study, passive eddy current damping due to constant magnetic field around the flywheel of a mathematically designed inerter was computed through simulation, and the range of achievable damping rates due to parametric variations, for instance air gap and magnetic coverage, was evaluated. Results of the parametric analysis showed that the induced eddy current damping from a rack-and-pinion inerter's flywheel, considering the designed inertance as prerequisite, was at least capable of achieving 1500 Nsm-1. As the achievable damping was within the range of suitable damping rates for typical passenger vehicles, rotary eddy current damper was deemed applicable in passenger vehicle suspension employing parallel inerter.